Japanese tourism and travel culture - Anguis, Sylvie Guichard (Routledge, 2015)
This book examines Japanese tourism and travel, both today and in the past, showing how over hundreds of years a distinct culture of travel developed, and exploring how this has permeated the perceptions and traditions of Japanese society.